PENGARUH MODULUS KEHALUSAN PASIR PADA BETON DENGAN MIXED DESIGN METODE ACI - Hamid, Agus; Suraatmadja, Djuanda; Sihotang, Abinhot (Jurnal Teknik Sipil ITENAS, 2007)
Fineness modulus of sand was defined to be total number percentage of granular cumulative that is restrained over a standardized sieve in terms of a weight percentage. In a concrete mix design, the proportion of a coarse aggregate is dependent upon the percentage of fineness modulus of sand. The research is designed to examine any definition of fineness modulus of sand begins at fineness modulus in a concretemix. The amount of experimental materials are 3 to be used to each mixed composition. An experiment was conducted in a cylindrical experimental with 10 cm in diameter, 20 cm in height. The observation is conducted at 14 days, 21 days, 28 days with ACI method. The research shown that best fineness modulus of sand applied to 25 MPa quality concrete mix is a mixture with fineness modulus of sand of 2,63 – 3,38. While best fineness modulus of sand applied to 40 MPa quality concrete in concrete mix design are 3,32 – 3,38.